Realism 4°. Objects, weather and infrastructure in Ben Lerner's 10:04. Issue 5 (29th July 2017) - De Bruyn, Ben
ABSTRACT: A rare example of a contemporary climate-change novel, Ben Lerner's 10:04 joins reflections on our increasingly unrecognisable planet with a remarkably realist attention to everyday life. This paper examines three aspects of the book's environmentally inflected realism in more detail. In response to Adam Trexler's account of Anthropocene fiction, it begins by examining Lerner's expansive representation of global commodities and planetary memorials. Turning from objects to subjects, the paper subsequently enlists Roland Barthes's late work on reference to describe Lerner's attention to weird weather and its destabilising effects on our bodies and epiphanies. The analysis concludes with a discussion of the social infrastructure underlying the circulation of objects and subjects, highlighting the novel's emphasis on the community-building as well as resource-depleting dimensions of our petromodernity. Via these three steps, the paper demonstrates, first, the importance of a newly expansive mode of cultural memory, related to capitalism, weather and energy, and second, that not just science fiction but also modified forms of realism may play an important role in cultural responses to climate change.